Neonatal exposure to hypoxia induces early arterial stiffening via activation of lysyl oxidases. Issue 7 (11th April 2023) - Steppan, Jochen; Nandakumar, Kavitha; Wang, Huilei; Jang, Rosie; Smith, Logan; Kang, Sara; Savage, William; Bauer, Maria; Choi, Rira; Brady, Travis; Wodu, Bulouere Princess; Scafidi, Susanna; et al.
Abstract: Hypoxia in the neonatal period is associated with early manifestations of adverse cardiovascular health in adulthood including higher risk of hypertension and atherosclerosis. We hypothesize that this occurs due to activation of lysyl oxidases (LOXs) and the remodeling of the large conduit vessels, leading to early arterial stiffening. Newborn C57Bl/6 mice were exposed to hypoxia (FiO2  = 11.5%) from postnatal day 1 (P1) to postnatal day 11 (P11), followed by resumption of normoxia. Controls were maintained in normoxia. Using in vivo (pulse wave velocity; PWV) and ex vivo (tensile testing) arterial stiffness indexes, we determined that mice exposed to neonatal hypoxia had significantly higher arterial stiffness compared with normoxia controls by young adulthood (P60), and it increased further by P120. Echocardiography performed at P60 showed that mice exposed to hypoxia displayed a compensated dilated cardiomyopathy. Western blotting revelated that neonatal hypoxia accelerated age‐related increase in LOXL2 protein expression in the aorta and elevated LOXL2 expression in the PA at P11 with a delayed decay toward normoxic controls. In the heart and lung, gene and protein expression of LOX/LOXL2 were upregulated at P11, with a delayed decay when compared to normoxic controls. Neonatal hypoxia results in a significant increase in arterial stiffness in early adulthood due to aberrant LOX/LOXL2 expression. This suggests an acceleration in the mechanical decline of the cardiovascular system, that contributes to increased risk of hypertension in young adults exposed to neonatal hypoxia that may increase susceptibility to further insults. Abstract : Neonatal hypoxia accelerates arterial aging through lysyl oxidase‐like 2 activation in both systemic and pulmonary circulation. Created with BioRender.com .